Print Books and Ebooks: The New Equilibrium in an Academic Library - Wells, David; Sallenbach, Anita (2023)
This article looks back at ALIA’s prediction from 2013 that ‘library print and ebook collections will establish a 50:50 equilibrium by 2020 and that this balance will be maintained for the foreseeable future’ in the light of the experience at Curtin University Library. It revisits the findings of an article on the same topic published in 2015, and documents the situation at Curtin University Library as at 2022. It describes changes in the ebook environment and user attitudes over the past 6 years, as well as developments in the Library’s acquisition strategies and methods to increase ebook holdings, and the current state of the collection. The article finally provides a likely projection of the ebook and print book holdings situation at Curtin Library in 2050.